Smart structure with elastomeric contact surface for prosthetic fingertip sensitivity development. (14th August 2017) - Gu, Chunxin; Liu, Weiting; Yu, Ping; Cheng, Xiaoying; Fu, Xin
Abstract: Current flexible/compliant tactile sensors suffer from low sensitivity and high hysteresis introduced by the essential viscosity characteristic of soft material, either used as compliant sensing element or as flexible coverage. To overcome these disadvantages, this paper focuses on developing a tactile sensor with a smart hybrid structure to obtain comprehensive properties in terms of size, compliance, robustness and pressure sensing ability so as to meet the requirements of limited space applications such as prosthetic fingertips. Employing micro-fabricated tiny silicon-based pressure die as the sensing element, it is easy to have both small size and good mechanical performance. To protect it from potential damage and maintain the compliant surface, a rigid base and a soft layer form a sealed chamber and encapsulate the fixed die together with fluid. The fluid serves as highly efficient pressure propagation media of mechanical stimulus from the compliant skin to the pressure die without any hazard impacting the vulnerable connecting wires. To understand the pressure transmission mechanism, a simplified and concise analytic model of a spring system is proposed. Using easy fabrication technologies, a prototype of a 3 × 3 sensor array with total dimensions of 14 mm × 14 mm × 6.5 mm was developed. Based on the quasi-linear relationship between fluid volume and pressure, finite element modeling was developed to analyze the chamber deformation and pressure output of the sensor cell. Experimental tests of the sensor prototype were implemented. The results showed that the sensor cell had good sensing performance with sensitivity of 19.9 mV N −1, linearity of 0.998, repeatability error of 3.41%, and hysteresis error of 3.34%. The force sensing range was from 5 mN to 1.6 N.